Multiscale Composites: Assessment of a Feasible Manufacturing Process - R. Volponi; P. Spena; F. De Nicola; L. Guadagno (International Journal of Aerospace Engineering)
A very interesting field of research on advanced composite materials is the possibility to integrate new functionalities and specific improvements acting on the matrix of the composite by means of a nanocharged resin. In this way, the composite becomes a so-called “multiscale composite” in which the different phases change from nano to macro scale. For example, the incorporation of nanoscale conductive fillers with intrinsically high electrical conductivity could allow a tailoring of this property for the final material. The properties of carbon nanotubes (CNT) make them an effective candidate as fillers in polymer composite systems to obtain ultralight structural materials with advanced electrical and thermal characteristics. Nevertheless, several problems are related to the distribution in the matrix and to the processability of the systems filled with CNT. Existing liquid molding processes such as resin transfer molding (RTM) and vacuum-assisted resin transfer molding (VARTM) can be adapted to produce carbon fiber reinforced polymer (CFRP) impregnated with CNT nanofilled resins. Unfortunately, the loading of more than 0.3-0.5% of CNT can lead to high resin viscosities that are unacceptable for such kind of processes. In addition to the viscosity issues that are related to the high CNT content, a filtration effect of the nanofillers caused by the fibrous medium may also lead to inadequate final component quality. This work describes the development of an effective manufacturing process of a fiber-reinforced multiscale composite panel, with a tetra-functional epoxy matrix loaded with carbon nanotubes to increase its electrical properties and with GPOSS to increase its resistance to fire. A first approach has been attempted with a traditional liquid infusion process. As already anticipated, this technique has shown considerable difficulties related both to the low level of impregnation achieved, due to the high viscosity of the resin, and to the filtration effects of the dispersed nanocharges. To overcome these problems, an opportunely modified process based on a sort of film infusion has been proposed. This modification has given an acceptable result in terms of impregnation and morphological arrangement of CNTs in nanofilled CFRP. Finally, the developed infiltration technique has been tested for the manufacture of a carbon fiber-reinforced panel with a more complex shape.